Problematika Manajemen Pendidikan Islam: Studi Kasus di Sekolah SMA Plus Islamic Village Tangerang - Ulfah, Ulfah (INTIFA: Journal of Education and Language, 2024)
Education is the process of preparing students' future in achieving life goals effectively and efficiently. Islamic education, in this case, guides students in their personal development, both physically and spiritually, towards the formation of the main personality of students in the future which is based on Islamic laws. Islamic education as a value, namely the discovery of Islamic values in the education system. The problems and challenges that exist in Islamic Religious Education, both in learning and in its application, are multidimensional. Everything must have problems and challenges that must be faced and solutions found, especially in education. There are many problems in education that still need to be resolved. The author wants to study specifically the problems and challenges in Islamic Religious Education. There has been a lot of research on the problems of Islamic Religious Education, but it is still focused only on educators and school management. In fact, the problem of Islamic Religious Education does not only exist within an educational institution but is a problem for all elements of society, including the family. In this study the author wants to discuss and examine the problems of Islamic Religious Education in terms of the scope of education, namely school, family and society. This research uses qualitative methods, based on literature study.